Classification, yield to maturity determinants and valuation of Islamic debt securities - Safari, Meysam (2012)
Sukuk securities are new debt instruments introduced to market since less than two decades ago. The market has grown to about US$850 billion in just 16 years. Unlike conventional bonds, which have been studied thoroughly over some 6 decades, there is a dearth of studies on sukuk market behavior. This thesis aims to begin one by providing: (i) a new and comprehensive classification; (ii) exploratory findings on determinants of yield; (iii) a comparison of yields of sukuk and bond securities; (iv) charting new time-line cash flow charts; (v)establish first principles of valuation for sukuk; (vi) a comparison of actual price against theoretical prices computed using conventional theory. In particular objectives (iv) and (v) are critical for market practices as well as academic teaching. We collected primary and secondary data covering 2001-2011 for 11 countries: the data set had 37,000 observations. Apart from using descriptive and simple statistical methods to analyze sukuk,regression analyses are used to estimate empirical determinants of yield to maturity, tested by parametric and non-parametric methods. Granger Causality tests are applied to explore a central question as to whether there is a causality link between yields of sukuk securities and yields of conventional bonds. In valuation model development, mathematical techniques are applied to identify the principles that should be considered in constructing valuation models. After careful examination of mostly descriptive statistics, we propose a new classification to categorize underlying contracts based on the intrinsic nature of fund raising: Pure-Debt, Equity-based, and Asset-Backed. Furthermore, Yields are analyzed to determine what factors influence them using cross-sectional tests. Liquidity, country of domicile, issuer-country risk, promised payments‟ rate, maturity, and issue size are found to be significant factors affecting sukuk yields. Payment frequency and market sectors are not relevant. Importantly,the magnitudes of the factor effects are different in different sukuk types. An important finding is that Sukuk securities are different from conventional bonds. Data on sukuk and matched bonds of (i)government, (ii) central bank, (iii) agencies, (iv) financial institutions,and (v) corporate issues are tested via pair-wise tests. Tests on yield spreads suggest there is a significant difference between sukuk and bonds in 72 per cent of tested pairs. There is also no causal relation in Granger Causality tests between yields of two types of securities. Current market practices of pricing sukuk securities by means of typical conventional models are tested. Results show that there is a significant deviation between model-driven and market prices, questioning the use of bond formula. Using mathematical techniques, modified valuation models are proposed. Underlying Shariah consistent contractual specifications are taken into account. Price limit for musharakah sukuk securities is proposed. Most important finding is the nullifying of the assumption of sameness of sukuk and conventional bonds. This implies that conventional bond and sukuk certificates are intrinsically different, so market needs to develop new methods of valuation and measurements. Moreover, by providing classification as well as creating a foundation literature, a better understanding is possible for more advanced studies of this growing market. Our identification of determinants of yields to maturity and the development of valuation models will enable changes in practices to be adopted. More research may be done on building complex valuation models based on our time line flow charts of cash flow.